Psicologia, política e ética : histórias e personagens da política pública de assistência social - Dettmann, Ana Paula da Silva (2013)
Psychology, Politics and Ethics are presented as political strategies of life management and discuss the possibilities of intervention of Psychology in Politics under an ethical perspective of life. The aim of this research was to investigate psychologists view on Social Service Policy and the practices they develop. In order to achieve the objective, this study embraces a qualitative research paradigm, guided by Oral History and based on 11 testimonies of psychologists that act on that Espírito Santo policy and take part in Fórum Estadual dos trabalhadores do SUAS. The testimonies raised aspects about Psychology and Policy interrelated to qualification and performance. The stories and characters in Social Services policy lead to the everyday of work, sometimes interspersed with biopolitics strategies of control and resistance, that either reproduce rules and standardization or produce lines of flight, divert and take possible paths of other ways of life. Re-introduced under the shape of characters that speak through psychologists, the stories are named, such as O Carcereiro , O Capitão do Mato , O Leão de Chácaras e a Rainha de Copas . The perspective of an expanded clinic carries the possibilities of subject and society change, from a clinic and critical view of Psychology and Public Policies.